PRAKTIK PEMBIAYAAN HAWALAH BERBASIS DIGITAL PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) “SIMPUL BERKAH SINERGI” PERWAKILAN DAERAH PONTIANAK - Dodot Sudiyanto; Sri Deti, Neli (ADISAM PUBLISHER, 2025)
The context of this research is the Take Over Riba service product, this service product is intended for cooperative members who have joined for at least 12 months with the intention of transferring ribawi transactions from conventional financial institutions, and outside financial institutions to transactions that are in accordance with sharia. This service product does not use collateral, and without interest. This service product aims to release cooperative members from usury activities, and provide enthusiasm to improve the people's economy according to sharia. This research approach is a qualitative approach. The qualitative approach focuses more on process research, such as interactions between people in a community, the process of carrying out work, the development of a symptom or civilisation. In this study, researchers explained the aspects of hawalah financing at the savings and loan cooperative and sharia financing ‘Simpul Berkah Sinergi’ Pontianak Regional Representative. The results showed that conceptually the financing practice of takeover usury service products at KSPPS Simpul Berkah Sinergi Cooperative applies a hawalah contract with the imposition of ujrah or fee. The agreement is very cooperative and in accordance with sharia or sharia principles based on DSN Fatwa Number 58/DSN- MUI/V/2007 concerning hawalah bil ujrah, DSN Fatwa Number: 12/DSN-MUI/IV/2000 concerning hawalah, and DSN Fatwa Number 31/DSN-MUI/VI/2002 concerning Debt Transfer. While the inhibiting factor in the practice of take over usury financing is the ineffectiveness of the application of the hawalah contract in the take over usury service product, especially because the people who are members of the cooperative do not know the existence of a hawalah contract with the imposition of ujrah or fees. There needs to be regular socialisation to provide understanding to members in particular and other Muslim communities